The structure of schizotypal personality traits: a cross-national study. Issue 3 (17th July 2017) - Fonseca-Pedrero, E.; Debbané, M.; Ortuño-Sierra, J.; Chan, R. C. K.; Cicero, D. C.; Zhang, L. C.; Brenner, C.; Barkus, E.; Linscott, R. J.; Kwapil, T.; Barrantes-Vidal, N.; Cohen, A.; et al.
Abstract : Background: Schizotypal traits are considered a phenotypic-indicator of schizotypy, a latent personality organization reflecting a putative liability for psychosis. To date, no previous study has examined the comparability of factorial structures across samples originating from different countries and cultures. The main goal was to evaluate the factorial structure and reliability of the Schizotypal Personality Questionnaire (SPQ) scores by amalgamating data from studies conducted in 12 countries and across 21 sites. Method: The overall sample consisted of 27 001 participants (37.5% males, n = 4251 drawn from the general population). The mean age was 22.12 years (s.d. = 6.28, range 16–55 years). The SPQ was used. Confirmatory factor analysis (CFA) and Multilevel CFA (ML-CFA) were used to evaluate the factor structure underlying the SPQ scores. Results: At the SPQ item level, the nine factor and second-order factor models showed adequate goodness-of-fit. At the SPQ subscale level, three- and four-factor models displayed better goodness-of-fit indices than other CFA models. ML-CFA showed that the intraclass correlation coefficients values were lower than 0.106. The three-factor model showed adequate goodness of fit indices in multilevel analysis. The ordinal α coefficients were high, ranging from 0.73 to 0.94 across individual samples, and from 0.84 to 0.91 for the combined sample. Conclusions: The results are consistent with the conceptual notion that schizotypal personality is a multifaceted construct and support the validity and utility of SPQ in cross-cultural research. We discuss theoretical and clinical implications of our results for diagnostic systems, psychosis models and cross-national mental health strategies.